The Relationship Between Cadres Knowledge And Motivation With Pneumonia Case Finding In Toddlers At Paal V Public Health Center In Jambi City - Nora Jenniririn Nainggolan; Dwi Noerjoedianto; M. Ridwan; Budi Aswin; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2026)
Pneumonia remains a leading cause of child mortality globally and in Indonesia. This study aims to analyze the relationship between knowledge and motivation of health cadres and their performance in finding pneumonia cases among toddlers at the Paal V Public Health Center, Jambi City. A quantitative cross-sectional design was employed with 67 female cadres as respondents. Data were collected using questionnaires and analyzed using the Chi-Square test. The results showed no significant relationship between education level and case finding (p = 0.900). However, a significant relationship was found between motivation and pneumonia case finding (p = 0.016). These findings suggest that enhancing cadre motivation is crucial for improving pneumonia detection in the community.